The intrahepatic signalling niche of hedgehog is defined by primary cilia positive cells during chronic liver injury - Grzelak, C.; Martelotto, L.; Sigglekow, N.; Patkunanathan, B.; Ajami, K.; Calabro, S.; Dwyer, Benjamin; Tirnitz-Parker, Janina; Watkins, D.; Warner, F.; Shackel, N.; McCaughan, G. (Elsevier BV, 2014)
Background & Aims: In vertebrates, canonical Hedgehog (Hh) pathway activation requires Smoothened (SMO) translocation to the primary cilium (Pc), followed by a GLI-mediated transcriptional response. In addition, a similar gene regulation occurs in response to growth factors/cytokines, although independently of SMO signalling. The Hh pathway plays a critical role in liver fibrosis/regeneration; however, the mechanism of activation in chronic liver injury is poorly understood. This study aimed to characterise Hh pathway activation upon thioacetamide (TAA)- induced chronic liver injury in vivo by defining Hh-responsive cells, namely cells harbouring Pc and Pc-localised SMO. Methods: C57BL/6 mice (wild-type or Ptc1+/_) were TAA-treated. Liver injury and Hh ligand/pathway mRNA and protein expression were assessed in vivo. SMO/GLI manipulation and SMO dependent/ independent activation of GLI-mediated transcriptional response in Pc-positive (Pc+) cells were studied in vitro. Results: In vivo, Hh activation was progressively induced following TAA. At the epithelial-mesenchymal interface, injured hepatocytes produced Hh ligands. Progenitors, myofibroblasts, leukocytes and hepatocytes were GLI2+. Pc+ cells increased following TAA, but only EpCAM+/GLI2+ progenitors were Pc+/SMO+. In vitro, SMO knockdown/hGli3-R overexpression reduced proliferation/viability in Pc+ progenitors, whilst increased proliferation occurred with hGli1 overexpression. HGF induced GLI transcriptional activity independently of Pc/SMO. Ptc1+/_ mice exhibited increased progenitor, myofibroblast and fibrosis responses. Conclusions: In chronic liver injury, Pc+ progenitors receive Hh ligand signals and process it through Pc/SMO-dependent activation of GLI-mediated transcriptional response. Pc/SMO-independent GLI activation likely occurs in Pc_/GLI2+ cells. Increased fibrosis in Hh gain-of-function mice likely occurs by primary progenitor expansion/proliferation and secondary fibrotic myofibroblast expansion, in close contact with progenitors.